The application of last in first out principle in retrenchment cases / Azureen Sahira Sauffee Afandi and Muhammad Iskandar Zainol - Sauffee Afandi, Azureen Sahira; Muhammad Iskandar, Zainol (2007)
Retrenchment is an industrial practice and at times it is inevitable. The employer might have to resort to such measures in ensuring the running of their business. One of the ways to retrench the employees is through the application of LIFO principle. The Last in First Out (LIFO) principle has been the chosen practice among the employer in the process of retrenchment. This principle is a mere guideline and is not binding to the employer. As a result, its application is open to exploitation and abuse. It is essential to understand the nature and the application of this principle. Although it is merely a guideline, it plays a very prominent role in most retrenchment cases. Since this principle has no legal effects, it is the intention of this project paper to clearly set out the confusion surrounding this area of Industrial Law. The nature, application and the departure of this principle will be determined and the process of retrenchment and the connection between retrenchment and LIFO principle itself will be discussed. This is important to establish the relevance of this process.